2023
DOI: 10.1039/d2se01377k
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol to diesel: a sustainable alternative for the heavy-duty transportation sector

Abstract: In this work, we explore the catalytic upgrading of ethanol into diesel following an approach based on the initial Guerbet coupling of ethanol followed by etherification. The results presented are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…1, the actual products of the alcohol oligomerization reactor also include small concentrations of esters. 2 Depending on the conversion of the oligomerization reactor, the ester concentration can range from less than 2%, to over 10%. Therefore, in this section, the introduction of esters in the dehydration reactor is analyzed to determine if these esters can also be upgraded into diesel-range molecules.…”
Section: The Effect Of Esters In the Reaction Streammentioning
confidence: 99%
See 3 more Smart Citations
“…1, the actual products of the alcohol oligomerization reactor also include small concentrations of esters. 2 Depending on the conversion of the oligomerization reactor, the ester concentration can range from less than 2%, to over 10%. Therefore, in this section, the introduction of esters in the dehydration reactor is analyzed to determine if these esters can also be upgraded into diesel-range molecules.…”
Section: The Effect Of Esters In the Reaction Streammentioning
confidence: 99%
“…Tuning the incoming alcohol feedstock to higher carbon numbers can lead to an increase in the diesel #2 yield, as fuel yield is an important economic factor in the ethanol to diesel process. 2 Our research team has shown that the C 10+ ethers can be maximized by feeding in a mixture of ethanol and butanol into the Guerbet reactor. 23 Fig.…”
Section: Dehydration Of Oligomerization Feeds From Ethanol and N-buta...mentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2,16] Besides the use as solvent or building block for plasticizers, [18,19] also an application of the obtained mixture of C 4 + alcohols as a direct source for bio-based fuels with high octane numbers that can for example directly be used in diesel engines is discussed. [1][2][3]11,20] Side-reactions include (transition metal-catalyzed) Cannizzaro and Tishchenko reactions, which both result in a steady consumption of base and, thus, a decline of reactivity. [1,2,16] A part of the network of reactions is shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%